Aerial plankton from the Eastern Tropical Pacific - Cotoras, Darko D.; Zumbado, Manuel A. (Revista de Biología Tropical, 2020)
Introduction: Small terrestrial invertebrates disperse in a passive manner through wind currents, forming what is known as aerial plankton, which has not been surveyed yet for the Eastern Tropical Pacific. Documenting the aerial plankton of Isla del Coco will allow to better understand the colonization process of this highly diverse island. Objective: Characterize the aerial plankton present on the transect Puntarenas – Isla del Coco. Methods: Specimens were collected using entomological nets on 2 roundtrip voyages during the months of July and August of 2017 and 2018, respectively. Results: A total of 10 morpho-species were collected corresponding to the orders: Diptera (Ceratopogonidae, Milichiidae, and Nematocera of a non-identified family), Hymenoptera (Chalcidoidea: Agaonidae), Hemiptera (Scutelleridae and Coreidae) and Lepidoptera (Sphingidae). Diptera and Hymenoptera were collected on the nets; while, Hemiptera and Lepidoptera were found on the deck of the boat. No spiders were collected. The Diptera and Hymenoptera families, as well as the family Coreidae (Hemiptera), have been previously recorded on this type of surveys across the tropical Pacific. Conclusions: Two of the taxa collected by nets, Ceratopogonidae (Diptera) and Chalcidoidea (Hymenoptera), have representatives on Isla del Coco, which could provide direct support for wind dispersal as a colonization mechanism for these groups. We also detected other insects (i.e. Lepidoptera and Scutelleridae-Hemiptera) which most likely reached the boat by their own means providing evidence of their dispersal abilities. This research provides data to further expand on questions about the mechanisms of island colonization.